2014
DOI: 10.1007/s12526-014-0241-4
|View full text |Cite
|
Sign up to set email alerts
|

Testing for nematode–granulometry relationships

Abstract: The majority of studies have advocated that diversity of marine nematodes increases with increasing sediment grain size, although the opposite trend has also been suggested. The controversy is partially caused by not taking into account the effect of density on patterns of diversity and by analyzing datasets from different environments. The present study investigated nematode assemblages from sediments varying from very fine sand (mean grain size of 0.12 mm) to very coarse sand (1 mm) in shallow sublittoral ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 31 publications
1
7
1
2
Order By: Relevance
“…Guerrini et al , 1998; Cibic et al , 2012; Boufahja et al , 2014; Semprucci et al , 2014a, 2016). Contrary to the general trends reported in literature (Danovaro et al , 2004; Semprucci et al , 2010; Fonseca et al , 2014), the stations characterized by the finest sediments (S6 and S7) showed the lowest meiofaunal abundances. Thus, although OM deposited in the sediments potentially has nutritional value for benthic consumers (Neira et al , 2001), all the meiofaunal major taxa appeared negatively affected by it.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Guerrini et al , 1998; Cibic et al , 2012; Boufahja et al , 2014; Semprucci et al , 2014a, 2016). Contrary to the general trends reported in literature (Danovaro et al , 2004; Semprucci et al , 2010; Fonseca et al , 2014), the stations characterized by the finest sediments (S6 and S7) showed the lowest meiofaunal abundances. Thus, although OM deposited in the sediments potentially has nutritional value for benthic consumers (Neira et al , 2001), all the meiofaunal major taxa appeared negatively affected by it.…”
Section: Discussioncontrasting
confidence: 77%
“…A strict relation between coarse sands and these two latter genera is, in fact, reported by several authors (e.g. Gheskiere et al, 2005;Fonseca et al, 2014).…”
Section: Discussionsupporting
confidence: 64%
“…In the context of marine ecosystems, meiobenthic habitats possess complex, dynamic interactions that are intricately combined and influenced by numerous abiotic factors 7 . The structure of the sediment is one of the main meiobenthic abiotic parameters, performing a leading role in meiobenthic ecology since its features influence the degree of accessibility of meiofaunal organisms 8,9 .…”
mentioning
confidence: 99%
“…Two studies have an experimental design. Fonseca et al (2014) test specifically whether nematode species richness increases with sediment mean grain size. They reject this hypothesis and show that along the sediment spectrum, each genus has a distinct optimum distribution at a relative narrow grain size.…”
Section: Ecologymentioning
confidence: 99%